Workshop for Preparation of Lecturers' Research Roadmap in Faculty of Teacher Training and Education, Tanjungpura University - Dyoty Auliya Vilda Ghasya; Y. Touvan Juni Samodra; Sesilia Seli; Uray Gustian; Rio Pranata; Lily Thamrin; Asriah Nurdini; Dian Miranda; Putri Tipa Anasi; Dwi Riyanti (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2023)
Roadmap itself is a road map and is devoted to mapping the journey of research. So that the research is more structured, can continue to grow, and produce something useful and easy to apply within a period of 5 to 20 years or even more. The research roadmap will help lecturers determine the research direction and then adjust it to the institution's priorities or higher education where they teach. The urgency of preparing the research roadmap above as well as the research roadmap document data for lecturers and undergraduate and masters level study programs within the FKIP Tanjungpura University who need to get refreshments. The Faculty Quality Assurance Unit team held a